Governing students’ self-development for character excellence in an Islamic boarding school: A POAC-based case study - Nova, Nova; Permana, Johar; Komariah, Aan; Sururi , Sururi (Indonesian Research Journal in Education |IRJE|, 2026)
This study explores how student self-development for character excellence is governed in an Islamic boarding school through the POAC framework: planning, organising, actuating, and controlling. Using a qualitative single-case design, the research was conducted at Pesantren Terpadu Almuslim, Bireuen, Indonesia, through semi-structured interviews, participatory observation, and document analysis involving leaders, teachers, dormitory supervisors, student mentors, students, parents, and alumni. The findings show that self-development is managed as an integrated system of character formation. Planning translates the pesantren’s vision into programmes, indicators, and annual work plans. Organising distributes roles across staff, students, families, and alumni. Actuating is reflected in religious routines, dormitory life, teacher role modelling, student leadership, extracurricular activities, and social service. Controlling is carried out through supervision, evaluation meetings, development records, and corrective guidance. Character excellence grows through this continuous cycle of daily pesantren life.